The feasibility and acceptability of a physical activity intervention for older people with chronic musculoskeletal pain: The iPOPP pilot trial protocol*. (8th December 2017) - Healey, E.L.; Jinks, C.; Foster, N.E.; Chew‐Graham, C.A.; Pincus, T.; Hartshorne, L.; Cooke, K.; Nicholls, E.; Proctor, J.; Lewis, M.; Dent, S.; Wathall, S.; et al.
Abstract: Introduction: This pilot trial will inform the design and methods of a future full‐scale randomized controlled trial (RCT) and examine the feasibility, acceptability and fidelity of the Increasing Physical activity in Older People with chronic Pain (iPOPP) intervention, a healthcare assistant (HCA)‐supported intervention to promote walking in older adults with chronic musculoskeletal pain in a primary care setting. Methods and analysis: The iPOPP study is an individually randomized, multicentre, three‐parallel‐arm pilot RCT. A total of 150 participants aged ≥65 years with chronic pain in one or more index sites will be recruited and randomized using random permuted blocks, stratified by general practice, to: (i) usual care plus written information; (ii) pedometer plus usual care and written information; or (iii) the iPOPP intervention. A theoretically informed mixed‐methods approach will be employed using semi‐structured interviews, audio recordings of the HCA consultations, self‐reported questionnaires, case report forms and objective physical activity data collection (accelerometry). Follow‐up will be conducted 12 weeks post‐randomization. Collection of the quantitative data and statistical analysis will be performed blinded to treatment allocation, and analysis will be exploratory to inform the design and methods of a future RCT. Analysis of the HCA consultation recordings will focus on the use of a checklist to determine the fidelity of the iPOPP intervention delivery, and the interview data will be analysed using a constant comparison approach in order to generate conceptual themes focused around the acceptability and feasibility of the trial, and then mapped to the Theoretical Domains Framework to understand barriers and facilitators to behaviour change. A triangulation protocol will be used to integrate quantitative and qualitative data and findings.